THE ROLE OF TOURISM AND ITS CONTRIBUTION TO THE GOVERNMENT OF UZBEKISTAN - Tuxtayeva Aziza Ilhom qizi; Teshaboyeva Nafisa Zubaydullayevna (PEDAGOGS, 2024)
Annotation: Nestled at the heart of the Silk Road, Uzbekistan boasts a captivating tapestry of ancient cities, stunning landscapes, and vibrant cultural traditions. In recent years, the nation has recognized the immense potential of tourism as a driver of economic growth, social development, and cultural preservation. This article delves into the multifaceted role of tourism in Uzbekistan, exploring its contributions to the government and its positive impact on various aspects of Uzbek society. From generating foreign exchange and creating jobs to promoting cultural heritage and empowering local communities, tourism has emerged as a vital force shaping the nation's path towards a prosperous and sustainable future. This article explores the multifaceted role of tourism and its positive impact on various aspects of Uzbek society.